Lung-selective mRNA delivery of synthetic lipid nanoparticles for the treatment of pulmonary lymphangioleiomyomatosis - Qiu, Min; Tang, Yan; Chen, Jinjin; Muriph, Rachel; Ye, Zhongfeng; Huang, Changfeng; Evans, Jason; Henske, Elizabeth P.; Xu, Qiaobing (Proceedings of the National Academy of Sciences - PNAS, 2022)
Safe and efficacious systemic delivery of messenger RNA (mRNA) to specific organs and cells in vivo remains the major challenge in the development of mRNA-based therapeutics. Targeting of systemically administered lipid nanoparticles (LNPs) coformulated with mRNA has largely been confined to the liver and spleen. Using a library screening approach, we identified that N-series LNPs (containing an amide bond in the tail) are capable of selectively delivering mRNA to the mouse lung, in contrast to our previous discovery that O-series LNPs (containing an ester bond in the tail) that tend to deliver mRNA to the liver. We analyzed the protein corona on the liver- and lung-targeted LNPs using liquid chromatography–mass spectrometry and identified a group of unique plasma proteins specifically absorbed onto the surface that may contribute to the targetability of these LNPs. Different pulmonary cell types can also be targeted by simply tuning the headgroup structure of N-series LNPs. Importantly, we demonstrate here the success of LNP-based RNA therapy in a preclinical model of lymphangioleiomyomatosis (LAM), a destructive lung disease caused by loss-of-function mutations in the Tsc2 gene. Our lung-targeting LNP exhibited highly efficient delivery of the mouse tuberous sclerosis complex 2 (Tsc2) mRNA for the restoration of TSC2 tumor suppressor in tumor and achieved remarkable therapeutic effect in reducing tumor burden. This research establishes mRNA LNPs as a promising therapeutic intervention for the treatment of LAM.